Effectiveness of innovator dydrogesterone versus generic dydrogesterone in early pregnancy: a real-world analysis - Jamwal, Sunita; Gudibanda, Sandeep; Shah, Snehal; Kaloo, Supriya; Sharma, Malvika; Miglani, Vaibhav; Govindaraj, Jayanthy; Verma, Garima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Miscarriage is the most common complication of early pregnancy. Dydrogesterone, a retro-steroid with high oral bioavailability and receptor selectivity, is widely prescribed to support and maintain pregnancy via its novel immunomodulation mechanism. There is a lack of comparative data on the miscarriage rate for pregnant females prescribed innovator, generic, and no dydrogesterone in early pregnancy. This study aimed to evaluate this comparative rate in real-world settings. Methods: A real-world, retrospective, observational study was conducted using anonymized and aggregated medical records from January 2017 to October 2024. Early pregnancy females (18-45 years) who consulted gynecologists were included. These were categorized into three arms: innovator dydrogesterone (Arm 1), generic dydrogesterone (Arm 2), and no dydrogesterone (Arm 3). These arms were balanced by propensity score matching (PSM), and miscarriage rates were compared using the Chi-square test. Results: The incidence of miscarriage was significantly lower in the innovator arm (4.10%) compared to Arm 2 (5.54%, p=0.040) and arm 3 (12.46%, p<0.001). No event of miscarriage was reported among women who switched from generic to innovator dydrogesterone. However, one of the females who shifted from innovator to generic experienced a loss of pregnancy. Conclusions: Innovator dydrogesterone was associated with the lowest rate of miscarriage compared to generic and no dydrogesterone. This suggests its potential clinical benefits in early pregnancy.